Aortic transection for resection of middle mediastinal tumor. Issue 1 (2nd January 2023) - Bierler, Julie; Poncelet, Alain; Lacroix, Valérie
Abstract: Background: Visceral mediastinal tumors are rare with challenging surgical approaches due to their location in close proximity with the great vessels and the pulmonary trunk. The aim of this paper is to discuss surgical strategies for complex cases of primary mediastinal tumors Methods: We present two cases of patients with middle mediastinal tumor, one synovial sarcoma and one paraganglioma. For both patients, surgical access was performed through a sternotomy with beating heart cardio-pulmonary bypass and aortic transection, allowing optimal exposure of the carina, of the common pulmonary artery and its bifurcation. Both tumors were resected 'en-bloc'. The postoperative course was uneventful and the two patients had a 3 months postoperative follow-up CT-scan showing no evidence of recurrence. Results: Surgery remains the cornerstone of treatment for synovial sarcoma and for paraganglioma of the visceral mediastinum and this location may be difficult to deal with. Many different surgical accesses exist and our approach of ascending aortic transection allows optimal exposure to the pulmonary artery, but also provides access to the upper airways. Conclusion: For visceral mediastinal tumor with close contact with vascular and respiratory structures, aortic transection allows an excellent exposure and control of the tumor with oncological resection.